2019
DOI: 10.1007/978-3-030-22750-0_52
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Parametric Linear Programming Solving, and Application to Polyhedral Computations

Abstract: Parametric linear programming is central in polyhedral computations and in certain control applications. We propose a task-based scheme for parallelizing it, with quasi-linear speedup over large problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Then, for given values of the μi, the problem is either unbounded, or there is one single optimal solution X ∗ . It can be shown that the region of the (μ1,,μk) associated to a given optimum X ∗ is a convex polyhedron (for C 0 , a convex polyhedral cone), and that these regions form a quasi‐partition of the space of parameters (two regions may overlap at their boundary, but not in their interior) 14,19,27 . The output of the parametric linear programming solver is this quasi‐partition, and the associated optima—in our applications, the problem is always bounded in the optimization directions, so we do not deal with the unbounded case.…”
Section: Sequential Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, for given values of the μi, the problem is either unbounded, or there is one single optimal solution X ∗ . It can be shown that the region of the (μ1,,μk) associated to a given optimum X ∗ is a convex polyhedron (for C 0 , a convex polyhedral cone), and that these regions form a quasi‐partition of the space of parameters (two regions may overlap at their boundary, but not in their interior) 14,19,27 . The output of the parametric linear programming solver is this quasi‐partition, and the associated optima—in our applications, the problem is always bounded in the optimization directions, so we do not deal with the unbounded case.…”
Section: Sequential Algorithmsmentioning
confidence: 99%
“…We are currently investigating approaches for getting rid of degeneracy—enforcing one optimal vector X ∗ and only one optimal basis per vector D , except at the boundaries. The methods for doing so rely on lexicographic orderings or perturbations on the objective and/or constant term, or pivoting rules 14 . We have recently proposed a working solution to degeneracy 28 but there is still room for improvement.…”
Section: Sequential Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…We extract the indices of the basic variables from that tableau; M B and O B denote the sub-matrices from M and B containing only the columns corresponding to the basic variables. By linear algebra in rational arithmetic 5 we compute a matrix Θ, representing the substitution performed by the simplex algorithm. Then we apply this substitution to the objective matrix O to get the new objective function…”
Section: Obtaining Rational Solutionmentioning
confidence: 99%
“…Furthermore, the solving is divided into independent tasks, which may be scheduled in parallel. The parallel implementation is covered in [5].…”
Section: Introduction and Related Workmentioning
confidence: 99%